Infected dentigerous cyst in the maxilla: Report of two cases - Nanda Pai; Samar Salim Shemna; Prerana N Dubey; Pratha Poddar (Wolters Kluwer Medknow Publications, 2020)
Dentigerous cyst (tooth-bearing), is the second-most common odontogenic cyst in the Indian population. They remain asymptomatic, causing pain and swelling only when infected. Many a times they are diagnosed only on routine radiography. This article presents two cases of infected dentigerous cyst in the maxilla, one of them being a rare occurrence of the cyst involving the maxillary sinus around the maxillary third molar.